Unlocking Investment Efficiency: Exploring ESG Practices through Management Control System Dynamics - Anis, Idrianita; Jansen Arsyah, Regina; Joseph, Corina; Hartini, Hartini; Tektona Agni, Muhammad (The Indonesian Journal of Accounting Research, 2024)
This study examines ESG practice's effect on Investment Efficiency (IE). This study develops an ESG practice model and index (ESGX) based on the management control system's four levers of control perspective (MCS-LoC). The ESGX is developed using content analysis of information disclosures in annual and sustainability reports. The ESGX score represents the company's policy capability maturity level. The research sample comprises non-financial industry sectors listed on the Indonesia Stock Exchange included in the SRI KEHATI and LQ45 Index from 2015 to 2022, totaling 212 firm-year observations. The study results show that sample companies are at the second stage of sustainable business transition (BST2.0; ESG score = 0.75 - < 0.90). The results show that ESG practice positively affects IE, and this finding is consistent in general and underinvestment scenarios. It indicates the Belief system's internalization and Diagnostic control used in determining strategic direction. The Boundary system has no effect, while the Interactive control system negatively affects IE. In the overinvestment scenario, ESGX has a marginally positive effect on IE, supported by the positive effect of the Belief, Diagnostic, and Interactive control system. In contrast, the boundary system does not affect IE, but an indication of positive effects is identified. The results confirm that ESG practice significantly improves IE by reducing information asymmetry and addressing agency problems by activating diagnostic and interactive control systems. The result gives implications for sustainable business practices in non-financial industry sectors and regulatory bodies.